Tenurial Conflict Resolution Analysis of Indigenous People of Pandumaan - Sipituhuta in Humbang Hasundutan District, North Sumatera Province - OK Hasnanda Syahputra; Anggraini, Novita (Talenta Publisher, 2023)
The customary forest area of Tombak Haminjon (incense forest) located in Pandumaan-Sipituhuta Village has high economic value but has challenges related to overlapping land management. This research aims to determine the history, parties, causes, and conflict resolution in this customary forest. This study used a qualitative approach and purposive sampling of key respondents and in-depth interviews with the stakeholders involved. The results showed that the factors causing the conflict were tenure conflicts. On the one hand, the Pandumaan-Sipituhuta customary forest as incense producer belonged to the indigenous peoples. On the other hand, PT Toba Pulp Lestari (TPL) has also claimed its concession area. The parties interested in using this forest area consist of Key actors, the main stakeholders, and the supporting stakeholders. The determination of customary forest in Pandumaan-Sipituhuta Village has met the requirements to be designated as customary forest after going through a data verification and validation mechanism by a multistakeholder team formed by the Ministry of Environment and Forestry. The determination of the Pandumaan-Sipituhuta customary forest has met the requirements to be designated as a customary forest after going through a verification and data validation mechanism by a multi-stakeholder team formed by the Ministry of Environment and Forestry. Therefore, as a recommendation, it is necessary to accelerate the demarcation of boundaries and the confirmation of the forest area.